Effects of proanthocyanidin enriched extract from Ligaria cuneifolia on plasma cholesterol and hemorheological parameters. In vivo and In vitro studies - Dominighini, Alicia (2014)
It was demonstrated that Ligaria cuneifolia (Lc) crude extract increased blood viscosity and decreased plasma cholesterol in rats. In the present study, we analyzed the Lc proanthocyanidin enriched fraction (PLc) to determine if it is capable of altering the hemorheological parameters while diminishing the plasma cholesterol. In vivo studies in adult male Wistar rats, randomized in three groups (n = 6 each one) were performed: 1. Control: saline intraperitoneal (i.p.); 2. PLc 0.6 mg/100 g body weight (b.w.) i.p. and 3. PLc 3 mg/100 g b.w. i.p., every 24 hours during 3 days. In vitro studies: with blood obtained by cardiac puncture, separated in aliquots and incubated with: 1. Saline solution (Control); 2. PLc 0.1 mg/mL, and 3. PLc 1.0 mg/mL, equivalent to doses in vivo experiments. The results demonstrated that in vivo PLc 0.6 and PLc 3 reduced plasma cholesterol (Cho) and LDL-Cho. Neither blood nor plasma viscosity was altered. Decrease of plasma cholesterol could be due to an increase of cholesterol and bile salts excretion leading to an increase of bile flow. In vitro experiments showed a direct interaction of PLc, at high concentration, with the erythrocyte membrane, inducing a switch from discocyte to stomatocyte. Only, PLc without hepatic metabolism produces hemorheological changes. Thus, PLc in vivo might be a pharmacological agent capable of decreasing plasma cholesterol.